2005
DOI: 10.1158/0008-5472.can-05-1288
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Radiosensitization by Antiinflammatory Drugs: Evidence for a New Mechanism Involving the Oxygen Effect

Abstract: We hypothesized that nonsteroidal antiinflammatory drugs (NSAIDs) might enhance tumor radiosensitivity by increasing tumor oxygenation (pO 2 ), via either a decrease in the recruitment of macrophages or from inhibition of mitochondrial respiration. The effect of four NSAIDs (diclofenac, indomethacin, piroxicam, and NS-398) on pO 2 was studied in murine TLT liver tumors and FSaII fibrosarcomas. At the time of maximum pO 2 (t max , 30 minutes after administration), perfusion, oxygen consumption, and radiation se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 34 publications
(50 reference statements)
4
52
0
Order By: Relevance
“…The decrease in perfusion is likely due to a vascular steal effect with a redistribution of the blood flow that feeds the tumor and the muscle. More recently, we observed that NS-398, an antiinflammatory agent, induced a similar effect in the same tumor model (15).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…The decrease in perfusion is likely due to a vascular steal effect with a redistribution of the blood flow that feeds the tumor and the muscle. More recently, we observed that NS-398, an antiinflammatory agent, induced a similar effect in the same tumor model (15).…”
Section: Discussionsupporting
confidence: 52%
“…2), showing that the perfusion is significantly reduced by NS-398. The value of Vp (plasmatic volume fraction) was unchanged, and the permeability (K trans and K ep ) was significantly decreased in this case (15).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Diclofenac is also widely used to treat pain associated with cancer, and treatment combinations of diclofenac with chemotherapeutic drugs are common. In addition, preclinical evidence is accumulating that NSAIDs, including diclofenac, have beneficial effects as adjuvant therapy in treatment of some types of cancer (Crokart et al, 2005;Johnsen et al, 2005). Due to this widespread co-use of drugs, interactions of NSAIDs with chemotherapeutic drugs can result in unexpected toxicities or failure of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…It has been predicted that modification of oxygen consumption is much more efficient at alleviating hypoxia than modification of oxygen delivery (10). Several drugs that inhibit mitochondrial respiration, such as metaiodobenzylguanidine (11), insulin (12,13), and cyclooxygenase-2 inhibitors (14), have been characterized for their potential to increase tumor oxygenation and thereby enhance radiosensitivity.…”
mentioning
confidence: 99%